Intravaginal administration of estradiol benzoate capsule for estrus synchronization in goats - Sayaka MATSUMOTO; Tomomi TANAKA; Natsumi ENDO (The Society for Reproduction and Development, 2021)
Estrus synchronization requires multiple treatments of hormonal drugs, requiring considerable time and cost. The aim of the present study was to develop an estrus synchronization protocol using intravaginal administration of estradiol benzoate (EB) capsules in goats. Two types of capsules were prepared: an EB capsule that melted immediately after administration and a sustained-release (SR) EB capsule that dissolved slowly and reached a peak after 24 h. Goats with functional corpus lutea were intramuscularly treated with prostaglandin F2α (PG). At 24 h after PG administration, goats were administered 1 mg of EB solution intramuscularly (PG + 24IM; n = 6) or 1 mg of EB capsule intravaginally (PG + 24EB; n = 6). The SR EB capsule was administered intravaginally at the time of PG administration (PG + SR; n = 6). The control group (n = 6) received only PG. All groups showed estrus within 72 h after PG administration. The onset of estrus did not differ significantly between the PG + 24IM and PG + SR groups but was earlier than in the control group. Estradiol concentration in the PG + SR group peaked at 11.5 ± 6.1 h after EB and PG administration. Peak estradiol concentrations were not significantly different between the PG + 24IM and PG + SR groups (78.0 ± 25.8 and 64.0 ± 38.1 pg/ml, respectively), and were higher than the PG + 24EB and control groups (27.3 ± 8.8 and 14.6 ± 6.1 pg/ml, respectively). These results suggest that intravaginal administration of an EB capsule with a sustained-drug release base is applicable for estrus synchronization, as an alternative to intramuscular administration.